Fort Atkinson Club summary survey report - Trechter, David; Janke, James (My University, 2013)
The purpose of this study was to gather opinions about the need for and willingness to pay for the various events/programs that might be offered at the redeveloped Fort Atkinson Club. The survey consisted of two versions. The first version was designed to assess potential use of the Fort Atkinson Club by businesses and organizations. The second version assessed personal/family use of the Club. Both surveys were administered online via Qualtrics survey software.
15 p.
Keywords: Fort Atkinson Club; Public opinion survey; UW Extension